Synovial chondromatosis of the distal radio-ulnar joint. Issue 6 (2nd November 2021) - Botros, David; Ford, Ken; Holderread, Brendan; Mollabashy, Al; Rizkalla, James
Abstract: Synovial chondromatosis (SC) is a benign metaplastic proliferation of cartilaginous nodules within the synovial membrane. Primary SC, though a rare monoarticular disease, significantly impacts patients' functional and pain-related outcomes. We outline the case of a 52-year-old man who presented with a large mass on the volar-ulnar aspect of his left wrist. Biopsy and workup revealed SC of the distal radio-ulnar joint. Though most cases of SC can be managed with arthroscopic or intralesional resection of the mass, a subset of extremely aggressive cases of SC may ultimately fail intralesional resection. Patients must be counseled about the possibility of amputation as an ultimate treatment option for the resolution of their pain and symptoms.